Comparison of homogeneous and heterogeneous catalysts in dye-sensitised photoelectrochemical cells for alcohol oxidation coupled to dihydrogen formation. Issue 22 (22nd October 2021) - Bruggeman, D. F.; Mathew, S.; Detz, R. J.; Reek, J. N. H.
Abstract : Dye-sensitised photoelectrochemical cells (DSPECs) for light-driven oxidative organic reactions and simultaneous reductive hydrogen production are reported, using TEMPO as catalyst/mediator either in homogeneous phase or immobilized on the electrode. Abstract : This study examines two strategies—homo- and heterogeneous approaches for the light-driven oxidation of benzyl alcohol in dye-sensitised photoelectrochemical cells (DSPECs). The DSPEC consists of a mesoporous anatase TiO2 film on FTO (fluorine-doped tin oxide), sensitised with the thienopyrroledione-based dye AP11 as the photoanode and an FTO–Pt cathode combined with a redox-mediating catalyst. The homogeneous catalyst approach entails the addition of the soluble 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO ) to the DSPEC anolyte, while the heterogeneous strategy employs immobilisation of a TEMPO analogue with a silatrane anchor (S-TEMPO ) onto the photoanode. Irradiation of the photoanode oxidises the TEMPO -moiety to TEMPO +, both in the homogeneous and the heterogeneous system, which is a chemical oxidant for benzyl alcohol oxidation. Photoanodes containing the heterogeneous S-TEMPO + demonstrate decreased photocurrent, attributed to introducing alternative pathways for electron recombination. Moreover, the immobilised S-TEMPO demonstrates an insufficient ability to mediate electron transfer from the organic substrate to the photooxidised dye, resulting in device instability. In contrast, the homogeneous approach with TEMPO as a redox-mediating catalyst in the anolyte is efficient in the light-driven oxidation of benzyl alcohol to benzaldehyde over 32 hours, promoted by the efficient electron mediation of TEMPO between AP11 and the organic substrate. Our work demonstrates that operational limitations in DSPECs can be solved by rational device design using diffusion-mediated electron transfer steps.